Kinetic study and characterization of sewage sludge for its incineration. Issue 3 (1st May 2008) - Mazza, G; Rodriguez, R; Flamant, G; Martinez, O; Gauthier, D; Udaquiola, S
Abstract : The sewage sludge from San Juan, Argentina, was characterized in an attempt to improve the thermal treatment efficiency and to reduce the environmental impact of incineration. The ash content is about 50% dry basis, and its weight loss at 105 °C was high. Taking into account the moisture content, it required drying for an autothermal combustion, thus imposing an additional combustible for incineration. The sludge contains high concentrations of several trace elements, and all but Hg are two to fivefold more concentrated in its ash. Thermogravimetric analyses were carried out on dry samples of sludge in inert and oxidative atmosphere. Three peaks can be observed in all differential thermogravimetric curves during the organic matter decomposition. The pyrolysis curve is over the combustion curve and parallel to it up to high temperatures. A kinetic model of the sludge weight loss during its incineration, based on these studies and combining the multi-step pyrolysis and combustion processes, is proposed and discussed.